2007
DOI: 10.1159/000108310
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction and telomerase activation in cancer – a pathological paradox?

Abstract: Telomerase is expressed in more than 90% of human cancers. Telomere maintenance by this enzyme is believed to safeguard genomic integrity in neoplastic cells. Nevertheless, many telomerase-expressing tumours exhibit chromosomal instability triggered by short, dysfunctional telomeres, implying that active telomerase is not sufficient for preserving a functional telosomic nucleoprotein complex in cancer cells. We here examine three possible solutions to this ostensible paradox. First, prior to telomerase activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 110 publications
1
10
0
1
Order By: Relevance
“…The reasons for this are unknown, but telomerase activity and telomere length change along very different time lines and under different circumstances, and thus may be unrelated. 40,58 Other reasons for the lack of significant correlations between telomere length and telomerase activity have been proposed, 68 including the shuttling of telomerase from the nucleus to the mitochondria under conditions of oxidative stress, 69,70 and the possibility that telomerase may decrease the number of PBMC’s with ‘short’ telomeres without significantly altering average PBMC telomere length. 61 It is possible that depression-related inflammation and/or oxidative stress contributed to our findings, as these may be associated both with shortened telomeres 7,15,71 and with stimulatory effects on telomerase activity 52–56 (although see ref.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are unknown, but telomerase activity and telomere length change along very different time lines and under different circumstances, and thus may be unrelated. 40,58 Other reasons for the lack of significant correlations between telomere length and telomerase activity have been proposed, 68 including the shuttling of telomerase from the nucleus to the mitochondria under conditions of oxidative stress, 69,70 and the possibility that telomerase may decrease the number of PBMC’s with ‘short’ telomeres without significantly altering average PBMC telomere length. 61 It is possible that depression-related inflammation and/or oxidative stress contributed to our findings, as these may be associated both with shortened telomeres 7,15,71 and with stimulatory effects on telomerase activity 52–56 (although see ref.…”
Section: Discussionmentioning
confidence: 99%
“…However there is a complete lack of detailed structural information about this ideal anticancer target. The different mechanisms of action of telomerase and its role in cancer chemotherapy have been recently reviewed by Calcagnile and Gisselsson [40]. Flavonoids have been considered in recent years as promising ligands for their use in cancer prevention and therapy [39].…”
Section: Telomerase Inhibiting Flavonoidsmentioning
confidence: 99%
“…GSK-3 is an attractive target for various diseases including Alzheimer's, bipolar disorder, diabetes, cancer and malaria. Even though the and isoforms are 97% identical with respect to their kinase domain, studies performed by Phiel et al [48] showed that selective reduction of and form leads to a decrease and increase in A 40 and A 42 (the primary constituents of the amyloid plaques in Alzheimer's disease), respectively. We previously investigated 4-arylmaleimide derivatives from Smith et al (VI) [49].…”
Section: Gsk-3 Inhibiting Maleimidesmentioning
confidence: 99%
“…This activation does not elongate telomeres; rather it prevents further telomere shortening. Thus, most cancers display short telomeres and robust telomerase activity (Calcagnile and Gisselsson, 2007; Kim et al, 1994). …”
Section: Introductionmentioning
confidence: 99%